Variations in leaf respiration across different seasons for Mediterranean evergreen species (PHOTOSYNTHETICA, 2013)
Leaf respiration (R (L)) of evergreen species co-occurring in the Mediterranean maquis developing along the Latium coast was analyzed. The results on the whole showed that the considered evergreen species had the same R (L) trend during the year, with the lowest rates \{[\}0.83 +/- 0.43 mu mol(CO2) m(-2) s(-1), mean value of the considered species] in winter, in response to low air temperatures. Higher R (L) were reached in spring \{[\}2.44 +/- 1.00 mu mol(CO2) m(-2) s(-1), mean value] during the favorable period, and in summer \{[\}3.17 +/- 0.89 mu mol(CO2) m(-2) s(-1)] during drought. The results of the regression analysis showed that 42% of R (L) variations depended on mean air temperature and 13% on total monthly rainfall. Among the considered species, C. incanus, was characterized by the highest R (L) in drought \{[\}4.93 +/- 0.27 mu mol(CO2) m(-2) s(-1)], low leaf water potential at predawn (I-pd= -1.08 +/- 0.18 MPa) and midday (I-md = -2.75 +/- 0.11 MPa) and low relative water content at predawn (RWCpd = 80.5 +/- 3.4%) and midday (RWCmd = 67.1 +/- 4.6%). Compared to C. incanus, the sclerophyllous species (Q. ilex, P. latifolia, P. lentiscus, A. unedo) and the liana (S. aspera), had lower R (L) \{[\}2.72 +/- 0.66 mu mol(CO2) m(-2) s(-1), mean value of the considered species], higher RWCpd (91.8 +/- 1.8%), RWCmd (82.4 +/- 3.2%), I-pd (-0.65 +/- 0.28 MPa) and I-md (-2.85 +/- 1.20 MPa) in drought. The narrow-leaved species (E. multiflora, R. officinalis, and E. arborea) were in the middle. The coefficients, proportional to the respiration increase for each 10A degrees C rise (Q(10)), ranging from 1.49 (E. arborea) to 1.98 (A. unedo) were indicative of the different sensitivities of the considered species to air temperature variation.

Leaf traits variation during leaf expansion in Quercus ilex L. (Photosynthetica, 2009)
The morphological, anatomical and physiological variations of leaf traits were analysed during Quercus ilex L. leaf expansion. The leaf water content (LWC), leaf area relative growth rate (RGRl ) and leaf dry mass relative growth rate (RGRm) were the highest (76±2 %, 0.413 cm 2 cm –2 d –1 , 0.709 mg mg –1 d –1 , respectively) at the beginning of the leaf expansion process (7 days after bud break). Leaf expansion lasted 84±2 days when air temperature ranged from 13.3±0.8 to 27.6±0.9 °C. The net photosynthetic rate (PN), stomatal conductance (gs ), and chlorophyll content per fresh mass (Chl) increased during leaf expansion, having the highest values [12.62±1.64 µmol (CO2) m –2 s –1 , 0.090 mol (H2O) m –2 s –1 , and 1.03±0.08 mg g –1 ,respectively] 56 days after bud break. Chl was directly correlated with leaf dry mass (DM) and PN. The thickness of palisade parenchyma contributed to the total leaf thickness (263.1±1.5 μm) by 47 %, spongy layer thickness 38 %, adaxial epidermis and cuticle thickness 9 %, and abaxial epidermis and cuticle thickness 6 %. Variation in leaf size during leaf expansion might be attributed to a combination of cells density and length, and it is confirmed by the significant (p<0.001) correlations among these traits. Q. ilex leaves reached 90 % of their definitive structure before the most severe drought period (beginning of June – end of August). The high leaf mass area (LMA, 15.1±0.6 mg cm –2 ) at full leaf expansion was indicative of compact leaves (2028±100 cells mm –2 ). Air temperature increasing might shorten the favourable period for leaf expansion, thus changing the final amount of biomass per unit leaf area of Q. ilex.

Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.

Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.

Adaptive photosynthetic strategies of the Mediterranean maquis species according to their origin (Photosynthetica, 2004)
In consideration of their origin the adaptive strategies of the evergreen species of the Mediterranean maquis were analysed. Rosmarinus officinalis L., Erica arborea L., and Erica multiflora L. had the lowest net photosynthetic rate (PN) in the favourable period [7.8±0.6 µmol(CO2) m -2 s -1 , mean value], the highest PN decrease (on an average 86 % of the maximum) but the highest recovery capacity (>70 % of the maximum) at the first rainfall in September. Cistus incanus L. and Arbutus unedo L. had the highest PN during the favourable period [15.5±5.2 µmol(CO2) m -2 s -1 , mean value], 79 % decrease during drought, and a lower recovery capacity (on an average 54 %). Quercus ilex L., Phillyrea latifolia L., and Pistacia lentiscus L. had an intermediate PN in the favourable period [9.2±1.3 µmol(CO2) m -2 s -1 , mean value], a lower reduction during drought (on an average 63 %), and a range from 62 % (Q. ilex and P. latifolia) to 39 % (P. lentiscus) of recovery capacity. The Mediterranean species had higher decrease in PN and stomatal conductance during drought and a higher recovery capacity than the pre-Mediterranean species. Among the pre-Mediterranean species, P. latifolia had the best adaptation to long drought periods also by its higher leaf mass per area (LMA) which lowered leaf temperature thus decreasing transpiration rate during drought. Moreover, its leaf longevity determined a more stable leaf biomass during the year. Among the Mediteranean species, R. officinalis was the best adapted species to short drought periods by its ability to rapidly recover. Nevertheless, R. officinalis had the lowest tolerance to high temperatures by its PN dropping below half its maximum value when leaf temperature was over 33.6 °C. R. officinalis may be used as a bioindicator species of global change.

Forecasted stability of Mediterranean evergreen species considering global changes (GLOBAL CHANGE AND PROTECTED AREAS, 2001)
Plant communities of the Mediterranean climate Regions are exposed to high temperatures, high radiation and water stress during summer, they are dominated by evergreen sclerophyllous species and drought semi deciduous species. To define the adaptive strategies, anatomical and morphological leaf traits of Quercus ilex L., Phillyrea latifolia L. (typical evergreen sclerophyllous species) and Cistus incanus L., (a drought semi deciduous species), growing in the Mediterranean maquis along Pome's coast line (Italy) were analysed. The typical evergreen sclerophyllous species have long leaf life span (from 1 to 4 years), steeper leaf inclination (average 56 degrees), higher specific leaf mass (average 21.3 mg cm(-2)) and the highest leaf thickness (average 324 mum). The semi deciduous species have a lower leaf life span (from 4 to 8 months), a lower leaf inclination (44 degrees +/- 13 degrees), a lower specific leaf mass (14.7 +/-1.5 mg cm(-2)) and a lower leaf thickness (244 +/- 15 mum). The more xeromorphyc species (Q. ilex and P. latifolia) may be at a competitive advantage considering the forecasted air temperature increase in the Mediterranean basin. Increasing drought stress may in fact determine a shortening of leaf life span that may prove to be critical for C. incanus. Knowledge of plant response to stress factors is important in the perspective of climatic changes.
Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999

Photosynthesis as a temperature indicator in Quercus ilex L. (Global and Planetary Change, 2000)
Net photosynthesis Pn , stomatal conductance gs , leaf temperature LT , transpiration rate . . . . E and in vivo chlorophyll fluorescence were monitored February 1996–February 1997 in Quercus ilex plants growing in the climax area Rome and . in the Garda lake region. Photosynthetic activity is an appropriate temperature-dependent functional trait linked to plant metabolism and performance. We employed photosynthesis as a stress temperature indicator. Regression analysis showed that in such regional climatic conditions, net photosynthetic rates were primarily correlated with temperature. The introduction of rainfall in the function did not significantly improve the theoretical prevision, in the range of temperature and rainfall analysed. The favourable leaf temperatures allowing 90–100% of the highest photosynthetic rates were 14–288C, decreasing over 50% when leaf temperature were respectively below 68C and over 378C: the low potential photochemical efficiency of 0.71 PSII Fv . rFm at Castelporziano during summer, confirmed the state of stress. Transpiration rates remained high with the increase of leaf temperature in summer, in spite of the 46% decrease of stomatal conductance. Nevertheless, this decrease allowed the maintenance of acceptable Pn rates in stressful conditions. The potential productivity of Q. ilex lied on high peaks of activity during periods of lower evaporative demand and a rapid stomatal response to an increase in air temperature and soil water deficit. Although it is difficult to forecast Q. ilex productivity and plant structure, we may hypothesize its future presence in the Mediterranean Basin by the capability of vegetative activity in a wide range of temperatures, the high stomatal control in stressful conditions, the high plasticity index and water use efficiency WUE .

Relationship between leaf life-span and photosynthetic activity of Quercus ilex in polluted urban areas (Rome). (Environmental pollution (Barking, Essex : 1987), 2000)
Anatomical, morphological and physiological leaf traits of Quercus ilex in response to different traffic levels (high traffic level, type A sites; average traffic level, type B sites; control sites, type C sites) were analysed in Rome. Superficial leaf deposits were analysed comparing unwashed and washed leaf samples. Washing lowered Pb 61% in A, 54% in B and 27% in C. Sr, Fe, Cu, Zn and Al showed the same trend as Pb. The higher photosynthetic activity of 1-year-old leaves (Pn=7.0+/-2.9 micromol m(-2 )s(-1), average value) in A sites with respect to B sites (6.7+/-2.4 micromol m(-2 )s(-1)) and C sites (6.7+/-1.8 micromol m(-2 )s(-1)) seems to be related to higher stomatal conductance (g(s)=0.13+/-0.06 mol m(-2 )s(-1)), higher total chlorophyll content (Chl=1.57 mg g(-1)) and higher leaf thickness (L(T)=218.9 microm), particularly palisade parenchyma thickness (109.4 microm). Q. ilex showed, on average, 95% of 1-year-old leaves and rarely 2-year-old leaves in A and B sites; 77% 1-year leaves, 20% previous-year leaves and sporadic 3-year leaves in C sites. The enhanced leaf senescence in A sites is compensated by a stimulated shoot production (18% higher with respect to C sites); 25% increased specific leaf area seems to be compensatory growth occurring in order to increase the size of the assimilatory area. The inverse trend of leaf life-span and Pn seems to be Q. ilex' adaptive strategy in polluted areas.

Leaf anatomy, inclination, and gas exchange relationships in evergreen sclerophyllous and drought semideciduous shrub species (PHOTOSYNTHETICA, 1999)
There are significant differences in leaf life-span among evergreen sclerophyllous species and drought semideciduous species growing in the Mediterranean maquis. Cistus incanus, which has a leaf life-span of four-eight months, was characterised by the highest net photosynthetic rates (PN). while Quercus ilex and Phillyrea latifolia, which maintain their leaves two-three and two-four years, respectively, had a lower PN- The longer leaf life-span of the two evergreen sclerophyllous species may be justified to cover the high production costs of leaf protective structures such as cuticle, hairs, and sclereids: cuticle and hairs screen radiation penetrating into the more sensitive tissues, and sclereids have a light-guiding function. Q. ilex and P. latifolia have the highest leaf mass/area ratio (LMA = 209 g m(-2)) and a mesophyll leaf density (2065 cells per mm(2) of leaf cross section area) about two times higher than C. incanus. In the typical evergreen sclerophyllous species the steepest leaf inclination (alpha = 56 degrees) reduces 42% of radiation absorption, resulting in a reduced physiological stress at leaf level, particularly in summer. C. incanus, because of its low leaf life-span, requires a lower leaf investment in leaf protective structures. It exhibits a drastic reduction of winter leaves just before summer drought, replacing them with smaller folded leaves. The lower leaf inclination (alpha = 44 degrees) and the lower LMA (119 g m(-2)) of C. incanus complement photosynthetic performance. Water use efficiency (WUE) showed the same trend in Q. ilex, P. latifolia, and C. incanus, decreasing 60% from spring to summer, due to the combined effects of decreased CO2 uptake and increased transpirational water loss.

Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.

Leaf and shoot growth dynamics of Quercus ilex L. (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1996)
The vegetative activity of Quercus ilex L. takes place during the period of low water stress, directly following abundant rainfall at the end of winter. Low air temperature is the limiting factor for bud opening, while high air temperature influences specific leaf area (SLA) during the growth period. Net photosynthesis and stomatal conductance increase with a rise in leaf temperature up to 25 degrees C; whereas they decrease when leaf temperature is about 30 degrees C (at the end of May) and below 18 degrees C (November). SLA increases from the low maquis to the shrubby layer of the forest in response to the decreasing irradiance. The pattern of SLA shows peak values after bud break, which then decrease to a constant value. Shrubs in the evergreen forest exhibit a high SLA in May as a result of a double increase in leaf area, while leaf dry weight changes only slighly during the first expansion. The maximum relative growth rate (RGR) in May-June causes the leaf to reach about 90% of its definitive size and structure before the period of drought stress, ensuring that leaf expansion (the time of the greatest nutritional demand) is not adversely affected. The summer air temperatures reduce the relative growth rate, but do not completely block leaf expansion until September-October. Intraspecific variation of SLA reflects the phenotypic plasticity of Quercus ilex in different habitats and demonstrates its ability to respond adequately to changing environmental factors by altering leaf morphology.

STRUCTURAL AND ECOPHYSIOLOGICAL PLASTICITY OF SOME EVERGREEN SPECIES OF THE MEDITERRANEAN MAQUIS IN RESPONSE TO CLIMATE (PHOTOSYNTHETICA, 1995)
The most representative evergreen shrub species growing in the low mediterranean maquis modified their leaf characteristics during the year, but the response to climate varied among the species. The real sclerophyllous species, Quercus ilex L., Phillyrea latifolia and Pistacia lentiscus, showed a convergence in higher leaf thickness and lower, net photosynthetic rate (PN) compared with Arbutus unedo L. and Cistus incanus L. Under summer stress they maintained a substantial positive carbon balance. Pistacia was one of the most tolerant species to the drought, it maintained a substantial positive balance over a wide range in temperature. Arbutus and Cistus had relatively thin leaves with a higher succulence index and higher PN over the more characteristic sclerophyllous species. The superiority of Cistus in carbon uptake over all the spacies was maintained throughout most of the year by its morphological leaf properties. low leaf thickness, high chlorophyll contents. Besides, Cistus shed most of its leaves before summer, thus reducing its evaporative surface.

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.

Morphological adaptions of Quercus ilex leaves in the Castelporziano forest (Plant Ecology, 1992)
The annual course of vegetative growth of the most representative species of a Ouercus ilex L. forest in Castelporziano (Latium, Italy) was studied through periodical analysis of selected ecophysiological leaf indexes, for the period 1987-1990. The results demonstrate that the local climate facilitates continuous vegetative activity of the sclerophyllous species without a latent phase. The variable morphology of sun and shade leaves of (2- ilex illustrates the plant's response to environmental stress.

A NONDESTRUCTIVE METHOD TO DETERMINE CHLOROPHYLL CONTENT OF LEAVES (PHOTOSYNTHETICA, 1992)
A reliable non-destructive method for determining leaf chlorophyll (Chl) content on site uses a simple instrument, the Minolta SPAD-502. Calibration curves plotting Chl-meter readings against Chl content extracted were obtained for various sclerophyllous species of a Quercus ilex L. evergreen forest.
APS

POSTFIRE RESPROUTING OF SHRUBBY SPECIES IN MEDITERRANEAN MAQUIS (VEGETATIO, 1991)
The vegetative resprouting of mediterranean maquis shrubby species was examined eight years after fire. Post-fire regeneration occurs through the resprouting of stumps. All species (Quercus ilex L., Phillyrea latifolia L., Arbutus unedo L., Erica arborea L., Pistacia lentiscus L.) show a rapid growth in the first years after fire, and a decrease already from 4th-5th year. All the species survived the fire and reconstituted a community similar to that unburned in a relatively short time span.